2017
DOI: 10.1002/pros.23349
|View full text |Cite
|
Sign up to set email alerts
|

Profile of cell proliferation and apoptosis activated by the intrinsic and extrinsic pathways in the prostate of aging rats

Abstract: Our findings reveal that, as the animals age, there is an increase of proliferation in restricted areas of the prostate epithelium, and a concomitant reduction of the apoptosis rate with an increase in cell survival induced by caspase-8, indicating a focused and spontaneous disruption of tissue homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…One of the main effects of the vitamin D signaling pathway on the prostate is the inhibition of cell proliferation, either by blocking the G1 to S phase cell cycle transition or by attenuating cell growth stimulating factors . Accordingly, the observed increase in VDR expression at 12 months onwards corroborates previous works from our laboratory showing that the normal prostate epithelium of older rats presents lower rates of cell proliferation than the prostate epithelium of young animals . In addition, the rat ventral prostate, which is the lobe less affected by spontaneous age‐related or androgen‐induced proliferative disorders, is also the region where we observed the highest VDR expression.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…One of the main effects of the vitamin D signaling pathway on the prostate is the inhibition of cell proliferation, either by blocking the G1 to S phase cell cycle transition or by attenuating cell growth stimulating factors . Accordingly, the observed increase in VDR expression at 12 months onwards corroborates previous works from our laboratory showing that the normal prostate epithelium of older rats presents lower rates of cell proliferation than the prostate epithelium of young animals . In addition, the rat ventral prostate, which is the lobe less affected by spontaneous age‐related or androgen‐induced proliferative disorders, is also the region where we observed the highest VDR expression.…”
Section: Discussionsupporting
confidence: 88%
“…Image analysis revealed that, although the nuclear VDR intensity did not change when positive epithelial cells were considered (Figure C), a significant increase in the number of VDR‐negative cells in IP areas was observed when compared to the adjacent normal epithelium (Figure D). As higher rates of cell proliferation are found in these punctual areas of the aging rat prostates, we investigated whether the increased number of cells lacking VDR were proliferating cells. Colocalization of VDR and the proliferation marker MCM7 revealed that many of the proliferating cells found in IP areas, but not in the adjacent normal epithelium, were also negative for VDR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations